2020
DOI: 10.35912/joste.v1i4.403
|View full text |Cite
|
Sign up to set email alerts
|

Innovative human resources management: key competencies expected from hospitality graduates in Ghana

Abstract: Purpose: The study aimed to determine the key competencies required from hospitality graduates from the hospitality industry perspective. Research Methodology: The study adopted a qualitative research approach. Overall, 43 hotel managers in the Ghanaian hospitality industry were conveniently sampled. Data were collected using a structured survey questionnaire. The study used Statistical Package for Social Sciences (IBM SPSS) version 23 to analysed data collected. Results: Results from the study indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…(Bappenas, 2020;M. Hasan & Azis, 2018) Although capacity development programs for human resources and organizations have been discussed in previous studies, several specific programs are planned in the marketing program to ensure successful planning and implementation (Commey, Kokt, & Hattingh, 2020).…”
Section: Placementioning
confidence: 99%
“…(Bappenas, 2020;M. Hasan & Azis, 2018) Although capacity development programs for human resources and organizations have been discussed in previous studies, several specific programs are planned in the marketing program to ensure successful planning and implementation (Commey, Kokt, & Hattingh, 2020).…”
Section: Placementioning
confidence: 99%
“…There are a number of considerations that employers must look at. The first is to ensure employees are equipped with the right competencies that will be valuable to the business (Commey et al, 2021). According to Lin and Wang, (2017), while new technologies have made it possible to communicate with people all over the world, they also have the potential to be disruptive because the constraints of distance is removed and the amount of work required is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The study identified 14 employability skills deficits in RHT and highlighted the most valued skills by employers in the hospitality and tourism sector. Similarly, Commey et al (2020) have stated that the key competencies of hospitality graduates include good interpersonal skills, leadership skills, problem-solving skills, teamwork, the ability to use technology, good decision-making skills, and good communication skills. Furthermore, Nawawi et al (2017) have argued that the hospitality industry in Malaysia requires 13 generic skills, which have been adopted from the Hospitality Skills Standards.…”
Section: Introductionmentioning
confidence: 99%